2015
DOI: 10.1007/s11136-015-0968-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between four health-related quality-of-life indicators and use of mammography and Pap test screening in US women

Abstract: Purpose Limited evidence is available to explain the role of four components of health-related quality of life (HRQoL) on breast and cervical cancer screening. The objective of this study was to determine the relationship between four HRQoL aspects and use of mammography and Pap test screening in US women. Methods Data were obtained from the 2012 Behavioral Risk Factor Surveillance System (BRFSS). The outcome variables were receiving mammogram <2 versus ≥2 years in women aged 50-74 years, and receiving Pap t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
5
14
1
Order By: Relevance
“…Ex-smokers were more likely than current smokers to be screened by both types of screening programs. Non-smokers were more likely than current smokers to participate in the organized screening program, which is in accordance with previous results regarding breast and cervical cancer screening among women in the United States [14]. We also found that light drinkers were more likely to be screened by both opportunistic and organized screening programs than non-drinkers, and the OR for opportunistic screening was higher than that for organized screening (OR, 1.36; 95% CI, 1.02 to 1.82 for opportunistic screening vs. OR, 1.26; 95% CI, 1.08 to 1.64 for organized screening).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ex-smokers were more likely than current smokers to be screened by both types of screening programs. Non-smokers were more likely than current smokers to participate in the organized screening program, which is in accordance with previous results regarding breast and cervical cancer screening among women in the United States [14]. We also found that light drinkers were more likely to be screened by both opportunistic and organized screening programs than non-drinkers, and the OR for opportunistic screening was higher than that for organized screening (OR, 1.36; 95% CI, 1.02 to 1.82 for opportunistic screening vs. OR, 1.26; 95% CI, 1.08 to 1.64 for organized screening).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have noted that individuals who engaged in physical activity or exercise were more likely to be screened for cancer [14]. Interestingly, we found no relationship between moderate physical activity more than 4 days per week and participating in screening.…”
Section: Discussioncontrasting
confidence: 63%
“…Several studies have demonstrated that frequent visits to medical doctors could increase opportunities to recommend breast cancer screening participation or promote awareness of cancer control [20,28,29], where those women who received medical treatment tended to undergo screening. The association between higher SRH and participation in breast cancer screening supports the ndings of previous research [55,56]. Individuals perceived as being in poorer physical health are less likely to participate in health checkups or screenings to avoid knowing the cause of their physical health status [57].…”
Section: Relationships Between Health Behaviors and Breast Cancer Scrsupporting
confidence: 80%
“…where those women who received medical treatment tended to undergo screening. The association between higher SRH and participation in breast cancer screening supports the ndings of previous research [55,56]. Individuals perceived as being in poorer physical health are less likely to participate in health checkups or screenings to avoid knowing the cause of their physical health status [57].…”
Section: Relationships Between Health Behaviors and Breast Cancer Scrsupporting
confidence: 80%